Answer:
x = 1[tex]\frac{1}{6}[/tex], y = 3[tex]\frac{2}{3}[/tex]
Step-by-step explanation:
y = -2x + 6 --- Equation 1
y = 4x - 1 --- Equation 2
Since both (-2x + 6) and (4x - 1) have the same total, y, they are equal.
-2x + 6 = 4x - 1
Isolate the like terms.
6 + 1 = 4x + 2x
Evaluate like terms.
6x = 7
Find x.
x = [tex]\frac{7}{6}[/tex]
x = 1[tex]\frac{1}{6}[/tex]
Substitute x = [tex]\frac{7}{6}[/tex] into Equation 2:
y = 4x - 1
y = 4([tex]\frac{7}{6}[/tex]) - 1
= 4[tex]\frac{2}{3}[/tex] - 1
y = 3[tex]\frac{2}{3}[/tex]